A hub-and-spoke design for ultra-cold COVID-19 vaccine distribution. Issue 41 (1st October 2021) - Xu, Xinglu; Rodgers, Mark D.; Guo, Weihong (Grace)
Highlights: A Hub-and-spoke network design model for COVID-19 phased vaccination campaign. Overcome ultra-cold facility shortage challenge without infrastructure investment. A new coverage model considering transportation accessibility and social vulnerability. Reduce temperature excursions and waste of ultra-cold vaccine via short-trip transfers. Abstract: An orderly and effective vaccination campaign is essential in combating the global COVID-19 pandemic. As one of the pioneers, the U.S. Center for Disease Control proposes a phased plan to promote the vaccination process. This plan starts with vaccinating the high-priority population in Phase 1, then turns to the remainder of the public in Phase 2, and ends with a scale-back network in Phase 3. The phased plan not only provides a sense of hope to impacted communities that this global pandemic can be defeated, but can serve as a template for other countries. To enhance this plan, this paper develops a generalizable framework for designing a hub-and-spoke vaccination dispensing network to achieve the goals in the Phase 2, which aims to expand the vaccination coverage for the general public. We introduce a new coverage index to measure the priority of different potential dispensing sites based on geo-data and develop an optimization model for network design. The hub-and-spoke network enhances the accessibility of the vaccines to various communities and helps to overcome the challenges related to ultra-cold storage facility shortage. A case study of Middlesex County in New Jersey is presented to demonstrate the application of the framework and provide insights for the Phase 2. Results from the baseline scenario show that increasing the driving time limit from 10 min to 25 min can improve the total coverage index from 40.8 to 55.9. Additionally, we explore how the changes of parameters impact the network design and discuss potential solutions for some special cases. When we allow 4 outreach nodes per hub, all potential 45 outreach points can be covered in the vaccination network within a 20-minute drive, and the total coverage index reaches its maximum value of 58.3.